Entomological surveillance, spatial distribution, and diversity of culicidae (diptera) immatures in a rural area of the atlantic forest biome, state of sao paulo, brazil - Piovezan, Rafael [UNESP]; Rosa, Stefany Larissa; Rocha, Matheus Luca; Azevedo, Thiago Salomão de; Von Zuben, Claudio José [UNESP] (Soc Vector Ecology, 2013)
Because of the high adaptive capacity of mosquitoes, studies that focus on transitional environments become very important, such as those in rural areas, which are considered as bridges between wild diseases and human populations of urban areas. In this study, a survey of the existing species of mosquitoes was performed in an Atlantic Forest area of the city of Santa Barbara d'Oeste, Sao Paulo state, Brazil, using traps for immatures and analyzing the frequency and distribution of these insects over the sampling months. Five mosquito species were found: Aedes albopictus (the most frequent species), Aedes aegypti, Aedes fluviatilis, Culex quinquefasciatus, and Toxorhynchites theobaldi. The 4,524 eggs collected in ovitraps showed the presence of the tribe Aedini. Aedes aegypti and Ae. albopictus were identified after larval hatching in the laboratory, with different spatial distributions: the first of which coincides with the area of greatest diversity calculated using the Simpson index, while the second does not. The association of ecological analysis of spatial diversity with simple methods of data collection enables the identification of possible epidemiological risk situations and is a strategy that may be implemented to monitor ecological processes resulting from the interaction among different species of mosquitoes.
Keywords: Aedes aegypti; Aedes albopictus; spatial distribution; surveillance; spatial diversity; ecology